Development of a Tough, Self-Healing Polyampholyte Terpolymer Hydrogel Patch with Enhanced Skin Adhesion via Tuning the Density and Strength of Ion-Pair Associations - Lee, Jin Hyun; Lee, Dae Sung; Jung, Yong Chae; Oh, Jeong-Wook; Na, Yang Ho (American Chemical Society, 2021)
Polyampholyte (PA) hydrogels have great potential for biomedical applications, owing to their high toughness and good self-recovery and self-healing (SELF) behavior in addition to their physical properties similar to human tissue. However, their implementation as practical biomedical skin patches or wearable devices has so far been limited by their insufficient transdermal adhesion strength. In this work, a new polyampholytic terpolymer (PAT) hydrogel with enhanced skin adhesion was developed using a novel and simple strategy that tunes the structure of ion-pair associations (IPAs), acting as cross-links, in the hydrogel via adding an extra neutral monomer component into the network without changing the total charge balance. The PAT hydrogels were synthesized by the terpolymerization of the neutral monomer N,N-dimethylacrylamide (DMAAm) (or 2-hydroxyethyl methacrylate (HEMA)) as well as the cationic monomer 3-(methacryloylamino) propyl-trimethylammonium chloride (MPTC) and the anionic monomer sodium p-styrenesulfonate (NaSS). Their IPA, which determines their network structure, was modulated by varying the feed concentration of the neutral monomer, C-nm. An increase of C-nm within an optimized C-nm window (0.3-0.4 M) decreased the cross-linking density (strength and density of the IPAs) of the PAT hydrogels, reducing the softening temperature and Young's modulus, which increased compliance but maintained sufficient mechanical strength and thereby maximized the contact surface and enhanced skin adhesion. The DMAAm monomers, compared to the HEMA monomers, produced the higher skin adhesion of the PAT hydrogel, which was explained by the difference in their reactivity to the MPTC and NaSS. This study demonstrated this new method to develop the PAT hydrogels with excellent skin adhesion and biocompatibility while maintaining good toughness, compliance, and SELF behavior and the potential of the PAT hydrogels for biomedical skin patches and wearable devices.